A Rare Cause of Hypopyon Anterior Uveitis: Relapsing Polychondritis - Nilüfer ZORLUTUNA KAYMAK,; Murat OKLAR,; Burak TANYILDIZ,; Mehmet Engin TEZCAN,; Şaban ŞİMŞEK, (Archives of Rheumatology, 2020)
Relapsing polychondritis (RP) is a rare multisystemic disease. It affects cartilage and proteoglycan-rich structures. Ocular findings are the most frequent systemic involvement of the disease. The most common ocular manifestations are episcleritis and scleritis. During the course of the disease, uveitis may also be seen. However, as far as we know, nongranulomatous anterior uveitis with hypopyon is an uncommon ocular finding. In this article, we report a 27-year-old male patient who presented with hypopyon anterior uveitis as a revealing manifestation of RP.